2018
DOI: 10.1111/jav.01790
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation versus historical isolation as sources of melanin‐based coloration in the white‐throated thrushTurdus assimilis

Abstract: Local adaptation seems to be one of the causes of variation in melanin‐based colors in bird plumages, related mainly to the heterogeneity of the environmental conditions along the distribution of a species. Based on comparisons of genetic (mtDNA sequences), ecological (niche models), and quantitative colorimetric data, we explored variation in plumage coloration of the white‐throated thrush Turdus assimilis, a Mesoamerican species whose dorsal color varies from brown (northern and central Mexico) to dark gray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
(88 reference statements)
0
2
1
Order By: Relevance
“…The lack of relationship between color variation and geographical distance indicates that the mechanism underlying this variation is not isolation by distance. This is in contrast to the findings of Núñez Zapata et al (2018) and by Ramírez-Barrera et al (2019) , who used a similar approach and found that for Turdus assimilis and Habia rubica respectively, Isolation by Distance is the model that best explains color variation. This, coupled with the lack of genetic structure that correlates to geography suggests that there may be more gene flow than previously thought and/or that carotenoid-based coloration in this species is fairly plastic.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of relationship between color variation and geographical distance indicates that the mechanism underlying this variation is not isolation by distance. This is in contrast to the findings of Núñez Zapata et al (2018) and by Ramírez-Barrera et al (2019) , who used a similar approach and found that for Turdus assimilis and Habia rubica respectively, Isolation by Distance is the model that best explains color variation. This, coupled with the lack of genetic structure that correlates to geography suggests that there may be more gene flow than previously thought and/or that carotenoid-based coloration in this species is fairly plastic.…”
Section: Discussioncontrasting
confidence: 99%
“…Chromatic and achromatic contrasts are expressed in just noticeable differences (JNDs) and indicate how different are two spectra perceived given the visual space of the receiver; values > 1 are considered discernible by birds [56,65] only under extremely controlled conditions [66,67]. Therefore, we used a conservative value of > 2 JNDs as the threshold above which visual discrimination could take place [68,69].…”
Section: Methodsmentioning
confidence: 99%
“…A large body of empirical data supports various ecogeographic rules (e.g., Meiri, 2011;Salewski & Watt, 2017 for Bergmann's rule; Betti et al, 2015;Laiolo & Rolando, 2001;VanderWerf, 2012;Yom-Tov & Yom-Tov, 2005 for Allen's rule; and Delhey, 2019 for Gloger's rule) although it is not uncommon to document exceptions to these rules (e.g., Núñez-Zapata et al, 2018;Riemer et al, 2018;Tattersall et al, 2017). Moreover, most of these studies focused on European and North American species (Betti et al, 2015;Delhey, 2019;Laiolo & Rolando, 2001;Meiri, 2011;Salewski & Watt, 2017;VanderWerf, 2012;Yom-Tov & Yom-Tov, 2005), and the rules remain to be tested against evolutionary lineages endemic to other geographic regions.…”
Section: Introductionmentioning
confidence: 99%